Activity of enisamium, an isonicotinic acid derivative, against influenza viruses in differentiated normal human bronchial epithelial cells. Issue 1 (November 2018) - Boltz, David; Peng, Xinjian; Muzzio, Miguel; Dash, Pradyot; Thomas, Paul G; Margitich, Victor
Aims: New therapeutics for the control of influenza virus infections are needed to alleviate the burden caused by seasonal epidemics and occasional pandemics, and to overcome the potential risk of drug-resistance emergence. Enisamium iodide (Amizon®, Farmak) is currently approved for clinical use for the treatment of influenza in 11 countries which includes Ukraine, Russia, Belarus, Kazakhstan, and Uzbekistan. However, experimental evidence of the antiviral activity of enisamium has not been reported. Methods: Antiviral activity of enisamium was assessed by virus yield reduction assays using differentiated normal human bronchial epithelial cells. Permeability of enisamium into differentiated normal human bronchial epithelial cells and its cytotoxicity were also assessed, and comparisons with other cell lines were made. Results: Enisamium inhibited replication of multiple subtypes of influenza A viruses, including seasonal H1N1, 2009 pandemic H1N1, seasonal H3N2, the zoonotic H5N1 and H7N9, neuraminidase inhibitor-resistant variant carrying the H275Y NA substitution (N1 numbering), and influenza B virus at doses 23- to 64-fold lower than cytotoxic concentrations. The permeability of enisamium in Madin–Darby canine kidney cells (where no antiviral activity was found) was less than 0.08%, while higher permeability was observed in differentiated normal human bronchial epithelial cells (1.9%). The kinetics of enisamium intracellular uptake in differentiated normal human bronchial epithelial cells was concentration dependent. In time-of-addition experiments in differentiated normal human bronchial epithelial cells, enisamium treatment within 4 h after A(H1N1) virus inoculation resulted in 100-fold or greater reductions in virus titers, suggesting that it affects an early stage of the virus life cycle. Conclusions: Enisamium exhibits antiviral activity against influenza viruses in vitro, supporting the reported clinical efficacy against influenza virus infections.